Working Environment and Professional Training: The True Human Resource Development - Escalante Guzmán, Giovanni (1998)
The Peruvian Ministry of Health is undertaking a health sector reform to reduce health gaps, to improve a universal and equitable access to efficient and quality services. Under this framework, human resources development has two basic dimensions: both population and health workers. The later depends on the former. There are problems regarding disagreements between professional training and health care services and population needs. Additionally, we found an asimetrical physician distribution, who were concentrated on biggest urban medical centers and hospitals. Overspecialized physicians and different problems to start working on rural areas have been observed. There is a need to set up a better link between academia and working on health through progresive education and open learning.